1983
DOI: 10.1111/j.1440-1827.1983.tb00352.x
|View full text |Cite
|
Sign up to set email alerts
|

FINE STRUCTURE OF HEPATIC SINUSOIDS and THEIR DEVELOPMENT IN HUMAN EMBRYOS and FETUSES

Abstract: The fine structure of the hepatic sinusoids of 81 human embryos and fetuses and their development from 5 to 12 weeks gestation were studied. At 5 weeks gestation, sinusoid‐like structures and Kupffer‐like cells were observed between liver cell cords. Between 6 and 8 weeks gestation the sinuosids were completely developed. Definite Kupffer cells appear at this developmental stage, when the bone marrow has not yet formed. Floating macrophages form cell aggregates in the sinusoids which contact endothelial cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 19 publications
1
43
0
Order By: Relevance
“…We have observed rounded, macrophage-like cells into the sinusoidal lumen, which showed a CCFSE/QH1 double labeling. Intraluminal clumps of macrophages had been described in the liver of human and mice embryos (Enzan et al, 1983(Enzan et al, , 1997Sasaki, 1990) and an origin from yolk sac has been proposed for these clumps (Sasaki, 1990). These intrasinusoidal macrophages disappear in later developmental stages (Kelemen and Janossa, 1980), perhaps by transendothelial migration and differentiation into Kupffer cells (Enzan et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have observed rounded, macrophage-like cells into the sinusoidal lumen, which showed a CCFSE/QH1 double labeling. Intraluminal clumps of macrophages had been described in the liver of human and mice embryos (Enzan et al, 1983(Enzan et al, , 1997Sasaki, 1990) and an origin from yolk sac has been proposed for these clumps (Sasaki, 1990). These intrasinusoidal macrophages disappear in later developmental stages (Kelemen and Janossa, 1980), perhaps by transendothelial migration and differentiation into Kupffer cells (Enzan et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…According to this view, the origin of sinusoid components should be found in the mesenchyme in which the liver anlage grows. In mammals, endo-thelial and stellate cells differentiate from the mesenchyme of the transverse septum in a typical process of vasculogenesis (Enzan et al, 1983(Enzan et al, , 1997Couvelard et al, 1996), although the origin of these vascular progenitors, as well as the precise mechanisms leading to the commitment and differentiation of the endothelial and stellate cells, are poorly known. In the avian embryo, however, the transverse septum develops relatively late, and the liver does not grow in a preexisting mesenchyme-rich environment.…”
Section: Introductionmentioning
confidence: 99%
“…19 Descriptive studies of both human and mouse development are consistent with the proposal that sinusoids develop through vasculogenesis of vessels that originate within the mesenchyme of the septum transversum. 5,19,20,23,24 In chick embryos, the septum transversum develops later than seen in mammals; however, lineage-tracing experiments have shown that the liver mesothelium may supplant the septum transversum as the origin of the hepatic sinusoids during avian development. 18 Hepatic stellate Fig.…”
Section: From Where Do Hepatic Cells Arise?mentioning
confidence: 99%
“…22 Although Kupffer cells are believed to develop from bone marrow-derived monocytes in adults, their presence in the fetal liver precedes bone marrow development, and they may originate from the yolk sac. 23 The sinusoidal capillaries and portal veins are among the first hepatic vessels to develop, with centrilobular veins and portal arteries forming later. 19 Descriptive studies of both human and mouse development are consistent with the proposal that sinusoids develop through vasculogenesis of vessels that originate within the mesenchyme of the septum transversum.…”
Section: From Where Do Hepatic Cells Arise?mentioning
confidence: 99%
“…Many macrophages were found in the yolk sac within 5 weeks of gestation (FUKUDA, 1973b) and in the liver at 6 to 8 weeks of gestation (ENZAN et al, 1983). On the other hand, hemopoiesis in bone marrow did not appear in the 8th week of ovulation (KELEMEN, CALVO and FLIEDNER, 1979).…”
Section: Discussionmentioning
confidence: 99%